The Influence of the Think-Pair-Share Cooperative Learning Model on Learning Outcomes on the Topic of Work and Simple Machines - Akuba, Siskawati; Odja, Abdul Haris; Buhungo, Trisnawaty Junus (Jurnal Pijar Mipa, 2025)
Science learning is often regarded as difficult by students due to the many concepts that are abstract and not well understood. Therefore, a learning model is required that can enhance students' academic performance. One of them is the cooperative learning model known as Think-Pair-Share (TPS), which encourages students to think independently, engage in paired discussions, and share ideas within their groups. This research aims to determine the effect of the Think-Pair-Share type cooperative learning model on the learning outcomes of simple machines and efforts in SMP Negeri 1 Kwandang. This study is an experimental research, utilising a one-group pretest-posttest Design. The sampling technique employed in this research is Cluster Random Sampling. The sample in this study uses class VIIIC as the experimental class, grouped through a random lottery. Data for this research were collected using a testing technique, which included normality tests, hypothesis tests, and n-gain tests. The analysis results indicate that the calculated values for all sample classes are greater than the tabulated values; thus, the hypothesis (H1) is accepted. The N-gain value of 0.80 indicates an improvement in learning outcomes that falls under the high category. The application of the Think-Pair-Share model, specifically for the material on simple machines and business, has rarely been researched before. This model has been proven to help students connect abstract concepts with real-life situations, fostering active participation in the learning process. Thus, the TPS type cooperative learning model has a significant impact on improving students' learning outcomes. This research also provides practical benefits as a basis for teachers to implement the cooperative model of Think Pair Share in learning to create a more active, effective, and meaningful learning atmosphere.